Ulnar Nerve Laceration — a Complication of Carpal Tunnel Decompression: Case Report and Review of the Literature - FAVERO, K. J.; GROPPER, P. T. (Journal of hand surgery, British volume, 1987)
Complications of peripheral nerve injury arising from the surgical treatment of carpal tunnel syndrome are not uncommon. No documented report of the association of ulnar nerve injury with carpal tunnel decompression has been found. This case-study describes partial laceration of the ulnar nerve as a complication of carpal tunnel surgery and reviews the literature on this subject.